Pengaruh Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Di Toko Bata Maumere - Naga, Alexis Rikardus; Rangga, Yoseph Darius Purnama; Yosef Tonce (Universitas Nusa Nipa Maumere, 2026)
The objective of this research is to determine the influence of brand image and product quality on purchase decisions at Bata Store Maumere. The problem in this study is based on the fluctuation of shoe product sales at Bata Store Maumere during 2025, which indicates that consumer purchase decisions are influenced by several factors, particularly brand image and product quality. This research uses a quantitative research method with a descriptive and inferential statistical approach. Data collection techniques were carried out through observation, interviews, questionnaires, and documentation. The population in this study is all consumers of the Bata Store Maumere, while the research sample was determined using specific sampling techniques according to research needs. The data analysis techniques used include validitytests, reliability tests, classic assumption tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination. The results show that brand image has a positive and significant effect on purchase decisions. Product quality also has a positive and significant effect on purchase decisions. Simultaneously, brand image and product quality have a significant effect on consumer purchase decisions at Bata Store Maumere. Therefore, the better the brand image and product quality, the higher the consumer's purchase decision towards the offered products.